PENGGUNAAN LAGU BERBAHASA JEPANG DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG (Penelitian Eksperimen Pada Siswa Kelas X IPS 1 SMA Muhammadiyah 1 Pekanbaru) - Raja Sirli Nur Andrian; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research discuss about the use of Japanese songs in learning Japanese vocabulary in the students of class X IPS 1 SMA Muhammadiyah 1 Pekanbaru. The purpose of this study is to know the mastery of Japanese vocabulary of students of class X IPS 1 SMA Muhammadiyah 1 Pekanbaru after using the Japanese language song in learning Japanese vocabulary. In this study, the writer used a weak experimental research design with marked by the absence of a class of comparison. The technique of collecting data by giving a test. Test results on pretest and posttest increase, on average prestest student score 70,8 whereas at posttest 91,2. The test results are processed using statistical t-test manually to find out how much the significant level of student learning outcomes when using Japanese songs. Based on statistical test data processing found t0 = 10,0 and tt = 2.63 (5% significant level), to tt then H0 rejected and Ha accepted, which means that there is a significant influence on the use of Japanese songs in improving the mastery of language vocabulary japanese students of class X IPS 1 SMA Muhammadiyah 1 Pekanbaru.Keywords: Learning Vocabulary, Japanese Language Song, SMA Muhammadiyah 1 Pekanbaru